A novel underwater measurement method for mooring system using self-contained technique. (18th May 2015) - Du, Yu; Wu, Wenhua; Tang, Da; Yue, Qianjin; Li, Feng; Xie, Ribin
This article introduces a prototype measurement method for investigating deep-water mooring systems. Measurement information and specifications are determined according to mooring system analysis. Mooring line information is difficult to measure underwater, particularly for aging platforms. To solve this problem, a novel mooring line tension measurement strategy based on lumped mass method is proposed. A type of self-contained sensor is designed and manufactured to realize dynamic response measurement of mooring systems underwater. The sensor is described in detail, including its design requirement, hardware design, and installation mode. A comprehensive field test system was constructed on a semi-submersible platform in South China Sea. Prototype data, including the data measured during typhoons, are introduced and discussed to improve the accuracy, feasibility, and stability of the proposed measurement method.